Islamic Philosophical Perspectives on Metaphysical Problems: A Study of the Works of Ibn Sina and Al-Ghazali - Amie Primarni; Etika Pujianti; Catherine Li; Jasafat Jasafat (Yayasan Adra Karima Hubbi, 2025)
Islamic philosophy offers profound insights into metaphysical problems, with the works of Ibn Sina (Avicenna) and Al-Ghazali standing as pivotal contributions. These scholars addressed foundational metaphysical issues, such as the nature of existence, causality, and the relationship between reason and revelation. This study investigates the metaphysical perspectives of Ibn Sina and Al-Ghazali, highlighting their intellectual interplay and enduring influence on Islamic and global philosophy. The research aims to compare and critically analyze their positions on key metaphysical problems, focusing on their interpretations of existence (wujud), causality, and the divine attributes. Employing a textual and comparative analysis method, the study examines primary sources, including Ibn Sina’s Al-Shifa and Al-Isharat wa al-Tanbihat, alongside Al-Ghazali’s Tahafut al-Falasifa and Al-Iqtisad fi al-I’tiqad. Secondary sources are utilized to contextualize their arguments within broader philosophical discourse. The findings reveal that Ibn Sina’s rationalist metaphysics emphasizes a hierarchical understanding of existence, while Al-Ghazali critiques such rationalism, emphasizing theological orthodoxy and divine omnipotence. This interplay demonstrates a dynamic intellectual tension that shaped the trajectory of Islamic metaphysics.